Penang and its networks of knowledge - Zabielskis, Peter; Yeoh, Seng Guan; Fatland, Kat (Areca Books, 2017)
This collection of contributions from a group of well known scholars highlights historic Penang's connections with the outside world, particularly how they were achieved and maintained. The port was established in the late 18th century to serve the region in the traffic of goods, but here we discover the cultural frameworks that evolved from and supported that trade.